2019
DOI: 10.1017/s0033291719001090
|View full text |Cite
|
Sign up to set email alerts
|

Functional connectivity in obsessive-compulsive disorder and its subtypes

Abstract: BackgroundObsessive-compulsive disorder (OCD) is an anxiety disorder with significant morbidity whose pathophysiology is not fully understood. Neuroimaging studies have characterized OCD in terms of elevated striatal and prefrontal reactivity to emotion provocation. This neural model may be informed by investigation of functional connectivity in OCD, identifying alterations in how sensory information is integrated into frontostriatal regions.MethodsThe current study employed functional magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 47 publications
3
17
2
Order By: Relevance
“…Consistent with the previous research, the present study discovered altered degree values within the CSTC circuit (i.e., left DLPFC and left thalamus) but failed to discover altered degree values in the emotional modulation network at rest in OCD. Different sample sizes, clinical symptoms, medication status, data analysis, and different OCD subtypes may account for these inconsistencies [59][60][61][62]. Moreover, inconsistent with our hypothesis, the current study did not find any relationship between degree values showing betweengroup differences and clinical variables in OCD.…”
Section: Discussioncontrasting
confidence: 95%
“…Consistent with the previous research, the present study discovered altered degree values within the CSTC circuit (i.e., left DLPFC and left thalamus) but failed to discover altered degree values in the emotional modulation network at rest in OCD. Different sample sizes, clinical symptoms, medication status, data analysis, and different OCD subtypes may account for these inconsistencies [59][60][61][62]. Moreover, inconsistent with our hypothesis, the current study did not find any relationship between degree values showing betweengroup differences and clinical variables in OCD.…”
Section: Discussioncontrasting
confidence: 95%
“… Reggente et al (2018) found in pre-treatment rsfMRI that the DMN and; in second place; the visual network (out of eight investigated networks) best predicted post-CBT treatment OCD severity (explaining 67% of the variance in posttreatment Y-BOCS). Tasked-based imaging studies in OCD patients by Stern et al (2017) ; as well as ( Ravindran et al, 2020 ); also involved visual areas and connectivity between DMN regions and occipital areas, similar to our findings. ( Ravindran et al, 2020 ) stimulated stress using OCD-related images and observed hyperactivation of the posterior cingulate gyrus (PCg), which is part of the DMN.…”
Section: Discussionsupporting
confidence: 89%
“…Tasked-based imaging studies in OCD patients by Stern et al (2017) ; as well as ( Ravindran et al, 2020 ); also involved visual areas and connectivity between DMN regions and occipital areas, similar to our findings. ( Ravindran et al, 2020 ) stimulated stress using OCD-related images and observed hyperactivation of the posterior cingulate gyrus (PCg), which is part of the DMN. Interestingly, this DMN region was hypoconnected with SN-related regions and hyperconnected with the left primary visual cortex.…”
Section: Discussionsupporting
confidence: 89%
“…Thirdly, OCD samples were not divided into different subtypes based on different clinical symptoms due to the sample characteristics (i.e., most patients (32/40) are mixed with both obsession and compulsion) and relatively small sample size. Different OCD subtypes may have different GFC patterns at rest (53). Future studies should consider these issues.…”
Section: Discussionmentioning
confidence: 97%